Uncovering How Sports Influence Adaptive Behavior in People with Disabilities: Examining Gender and Disability Type - Alzahrani, Abdulwahab Saeed; Alsayed, Abdulrahman k. (Journal of Ecohumanism, 2024)
This research aimed to investigate the relationship between sports and improvement of the adaptive behavior of people with disabilities, differences in the effect of sports on the improvement of adaptive behavior of people with disabilities in terms of (sex) variable and differences in the effect of sports on the improvement of adaptive behavior of people with disabilities in terms of (type of disability) variable. To achieve these aims, the researcher used the descriptive approach as well as the questionnaire to investigate the effect of practicing sports on the adaptive behavior skills of people with disabilities. The results of the research showed that there are no statistically significant differences at (0.05) concerning “sports and its effect on the adaptive behavior skills of people with disabilities” in terms of (sex) variable and that there are no statistically significant differences at (0.05) concerning “sports and its effect on the adaptive behavior skills of people with disabilities” in terms of (type of disability) variable. The researcher recommended the necessity of encouraging all people regardless of their sex to participate in the sports activities so as to enhance integration and help in improvement of the adaptive behavior skills of all people with disabilities.